High-binding-force antifouling anti-drag coating for titanium alloy base material as well as preparation method and application of high-binding-force antifouling anti-drag coating
Through microarc oxidation and hydrothermal treatment, and combined with dual network hydrogel technology, the problem of titanium alloy being damaged by marine biological pollution in the marine environment is solved, achieving high binding force, long-term and stable anti-fouling and drag reduction effect.
Patent Information
- Application Number
- CN202510001787.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-02
AI Technical Summary
Titanium alloys are susceptible to marine biofouling in the marine environment, resulting in increased flow resistance, reduced heat exchange efficiency, and may cause power device failure and corrosion under the stained layer.
The ceramic membrane is formed by microarc oxidation technology, combined with hydrothermal treatment, and introduced nano-scale porous puncture microstructure and hydroxyl groups. The coating prepolymer solution reacts under ultraviolet light to form a first network gel, and soaked in the β-glycerol phosphate sodium salt solution to form an ion-covalent dual network hydrogel.
It significantly improves the stability and durability of the coating, achieves long-term and stable anti-fouling performance and high binding force, significantly reduces marine biological adhesion and seawater friction resistance, and achieves excellent anti-fouling and drag reduction effect.
Smart Images

Figure CN119752267A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal material surface treatment, and in particular to a high-bonding anti-fouling and drag-reducing coating for a titanium alloy substrate, and a preparation method and application thereof. Background Art
[0002] As a manufacturing material for marine structures, titanium alloy has been widely used in marine equipment seawater pipeline projects due to its excellent properties such as high specific strength, strong corrosion resistance and light weight.
[0003] However, in the long-term marine environment, titanium alloy has good biocompatibility, which makes its surface face serious marine biofouling problems. These foulings not only increase the resistance of marine flow and reduce the heat transfer efficiency, but also may cause a series of effects such as power unit failure and corrosion under the fouling layer. For this reason, people have proposed to use zwitterionic hydrogels with high binding force as protective coatings for titanium alloy structures. This zwitterionic hydrogel not only combines the optimization of the material surface microstructure, but also realizes the intelligent regulation of the material surface wettability through its unique chemical composition design.
[0004] Traditional super-hydrophobic surfaces construct an air layer through surface micro-morphology and low surface energy modification, thereby forming a solid-gas-liquid three-phase interface. The air layer blocks direct contact between marine organisms and the solid surface, while also reducing the frictional resistance between the fluid and the surface, achieving the purpose of anti-fouling and drag reduction. The hydrogel surface forms a stable hydration layer on the surface through its internal microstructure and chemical composition, and utilizes its excellent water absorption and water retention capabilities. The hydration layer replaces the solid surface to form a liquid-liquid interface, thereby significantly reducing the contact area and adhesion between marine organisms and the surface of the structure. At the same time. The liquid-liquid interface further reduces the frictional resistance of seawater to the structure, achieving the effect of anti-fouling and drag reduction.
[0005] The superhydrophobic surface partially transforms the solid-liquid contact surface into a free shear surface of gas-liquid contact, forming an air cushion on the solid surface, thereby generating velocity slip and reducing viscous drag to achieve drag reduction. However, its three-phase surface energy barrier is easily destroyed at pipeline flow rates, and due to the rupture or depletion of the captured gas, the wetting state will change from the Cassie-Baxter state to the Wenzel state, resulting in the disappearance of drag reduction performance, and the same is true for superslippery surfaces. Therefore, thermodynamic instability hinders the long-term application of superhydrophobic (superslippery) surfaces. In addition, the hydration ability of hydrophilic coatings gradually weakens under high flow rates, resulting in the loss of their antifouling and drag reduction properties. Summary of the invention
[0006] In order to solve the deficiencies of the prior art mentioned in the above background technology, the present application provides a method for preparing a high-bonding anti-fouling and drag-reducing coating for a titanium alloy substrate, and the technical solution thereof is as follows: The preparation method of the coating with high bonding strength for anti-fouling and drag reduction of titanium alloy substrate provided in the present application comprises the following steps: Micro-arc oxidation: Micro-arc oxidation treatment is performed on titanium alloy to form a ceramic film on the surface of the titanium alloy; Hydrothermal treatment: subjecting the titanium alloy after micro-arc oxidation treatment to a hydrothermal reaction, introducing nano-scale porous thorn microstructures and hydroxyl groups on the surface of the ceramic membrane; Hydrogel coating: coating the prepolymer solution on the titanium alloy after hydrothermal treatment, and irradiating the reaction under ultraviolet light to obtain the first network gel; The prepolymer liquid is a yellowish viscous liquid formed by the reaction of the mixture at room temperature under a protective atmosphere; the mixture is a mixed solution formed by mixing chitosan, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide, α-ketoglutaric acid, and acrylic acid in water.
[0007] In some embodiments, after the first network gel is formed, the first network gel is post-treated; the post-treatment process is: immersing the first network gel in a β-glycerophosphate sodium salt solution to form an ionic-covalent double network p(SBMA-co-AAc) / CS-β-GP DN hydrogel.
[0008] In some embodiments, the prepolymer solution is coated on the titanium alloy after hydrothermal treatment, and the reaction is irradiated under ultraviolet light for 7 to 12 hours to obtain a first network gel; the first network gel is immersed in a β-glycerophosphate sodium salt solution for 0.5 to 8 hours to form an ionic-covalent double network p(SBMA-co-AAc) / CS-β-GP DN hydrogel; The preparation process of the prepolymer solution is as follows: dissolving chitosan and [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide in water to form a mixed solution; then adding α-ketoglutaric acid and acrylic acid to the mixed solution, reacting at room temperature for 10 to 20 minutes under a nitrogen atmosphere to obtain a slightly yellow viscous liquid; finally, eliminating bubbles in the slightly yellow viscous liquid to obtain a prepolymer solution; in the mixed solution, the mass ratio of chitosan to water is 1 to 10:100, and the prepolymer solution is preferably 100% water. The molar concentration of the [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide is 1 mol / L to 5 mol / L; the molar ratio of the α-ketoglutaric acid to the [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide is 0.1 to 2:100; and the molar ratio of the acrylic acid to the [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide is 1 to 10:100.
[0009] In some embodiments, the micro-arc oxidation process is as follows: placing an electrolyte in an electrolytic cell, then placing a titanium alloy in the electrolyte as an anode, and a metal sheet in the electrolytic cell as a cathode; starting a bipolar pulse micro-arc oxidation power supply to perform micro-arc oxidation treatment; and then cleaning the titanium alloy; wherein the electrolyte temperature during the entire micro-arc oxidation treatment is lower than 20°C, and a constant current mode is used throughout the process, with a current density of 0.5 to 2 mA / cm 2 , frequency is 300~2000Hz, duty cycle is 3~10%, deposition time is 300~1200s, and termination voltage is 400~650V.
[0010] In some embodiments, the components of the electrolyte include silicate, glycerol, potassium fluoride, phosphate, sodium hydroxide, and water; wherein the concentrations of silicate, glycerol, potassium fluoride, phosphate, and sodium hydroxide in the electrolyte are 5-15 g / L, 3-9 g / L, 0-10 g / L, 0-5 g / L, and 5-15 g / L, respectively; wherein the material of the metal sheet is stainless steel.
[0011] In some embodiments, the hydrothermal reaction process is: immersing the titanium alloy after micro-arc oxidation treatment in an alkaline solution preheated to 20-60°C, and immersing it at 20-60°C for 0.5-4h; then taking out the titanium alloy, immersing it in a dithiothreitol dilution, and then adjusting the pH of the dithiothreitol dilution to 6-6.5 with alkali, and stirring at room temperature for 10-60min, so that nano-scale microstructures and hydroxyl groups are introduced into the surface of the ceramic membrane.
[0012] In some embodiments, during the hydrothermal reaction, sodium hydroxide is used to adjust the pH of the dithiothreitol dilution solution; the alkali solution is a 1-8 wt % sodium hydroxide aqueous solution; the molar concentration of the dithiothreitol dilution solution is 0.01-0.05 mol / L; after the hydrothermal reaction is completed, the titanium alloy is taken out and stored at low temperature for later use.
[0013] In some embodiments, before the micro-arc oxidation treatment, the surface of the titanium alloy is polished and cleaned in sequence.
[0014] The present application also provides a high-bonding anti-fouling and drag-reducing coating for a titanium alloy substrate, which is prepared by the preparation method described above.
[0015] The present application also provides the application of the high-bonding anti-fouling and drag-reducing coating for titanium alloy substrates as described above on the surfaces of ships, bridges, docks, offshore platforms, petroleum, chemical industry, transportation, aviation and various titanium metal structures.
[0016] Based on the above, compared with the prior art, the method for preparing a high-bonding anti-fouling and drag-reducing coating for a titanium alloy substrate provided in the present application has the following beneficial effects: The coating prepared by the preparation method provided in the present application has improved stability and durability, and the coating has long-term stable anti-fouling performance. It is strongly bonded to the titanium alloy substrate and has excellent anti-fouling and drag reduction effects when applied to the titanium alloy substrate.
[0017] Other features and beneficial effects of the present application will be described in the subsequent description, and partly become apparent from the description, or understood by practicing the present application. The purpose and other beneficial effects of the present application can be realized and obtained by the structures specifically pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0019] Figure 1 The SEM morphology of titanium alloy surface under different treatment processes; Figure 2 FTIR-ATR (Fourier transform infrared spectroscopy) diagram of titanium alloy surface coating under different treatment processes; Figure 3 This is a diagram showing the pollution status of titanium alloy surfaces treated with different processes after 45 days of offshore hanging test; Figure 4 This is a curve of friction coefficient of titanium alloy surface under different treatment processes. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments; the technical features designed in different implementation modes of the present application described below can be combined with each other as long as they do not conflict with each other; based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0021] In the description of this application, it should be noted that all terms (including technical terms and scientific terms) used in this application have the same meanings as those generally understood by ordinary technicians in the field to which this application belongs, and cannot be understood as limitations on this application; it should be further understood that the terms used in this application should be understood to have meanings consistent with the meanings of these terms in the context of this specification and in the relevant fields, and should not be understood in an idealized or overly formal sense, unless explicitly defined in this application.
[0022] 1. This application provides the following embodiments and comparative examples: Example 1: Preparation of MAO-TA24-OH-p(AA-SBMA) / CS-β-GP DN Sample Step 1: Polishing and cleaning: First, the surface of titanium alloy TA24 was polished in sequence using 400#, 800#, 1200#, 2000#, and SiC sandpaper, and then ultrasonicated in deionized water and anhydrous ethanol for 15 minutes respectively, and then dried for later use, which was recorded as the polished TA24 sample.
[0023] Step 2, Micro-arc oxidation (MAO): Pour the prepared electrolyte into the electrolytic cell and stir in air for 10 minutes to fully dissolve it. Then place the cleaned and polished TA24 in the electrolyte as the anode, and the stainless steel sheet in the electrolytic cell as the cathode; start the bipolar pulse micro-arc oxidation power supply to carry out micro-arc oxidation treatment. Among them, the electrolyte temperature of the whole micro-arc oxidation treatment is controlled to be lower than 20°C through an external water cooling circulation device, and the micro-arc oxidation treatment adopts a constant current mode throughout the process, and the power supply setting parameters are: current density 1.5mA / cm 2 , frequency is 800 Hz, duty cycle is 6%, deposition time is 600 s, and termination voltage is 600 V. After the experiment, turn off the water cooling circulation device and the power switch, take out the sample, wash the sample with anhydrous ethanol, blow dry it and place it in a culture dish for later use.
[0024] The samples treated with MAO were recorded as MAO-x samples or MAO-TA24 (y) samples, where x- represents the MAO termination voltage and y represents the deposition time.
[0025] The electrolyte consists of silicate (Na2SiO3·9H2O), glycerol (C3H8O3), potassium fluoride (KF), phosphate (Na3PO3·12H2O), sodium hydroxide (NaOH), and water. All reagents are analytically pure. The concentrations of silicate, glycerol, potassium fluoride, phosphate, and sodium hydroxide are 15g / L, 6g / L, 7g / L, 2g / L, and 7g / L, respectively. Potassium fluoride is added to improve the conductivity of the solution.
[0026] Step 3, hydrothermal reaction: (1) Preparation of MAO-TA24 hydrothermal treatment samples The titanium alloy after micro-arc oxidation treatment was immersed in an alkaline solution preheated to 40°C for 4 hours to form a porous micro-nano structure on the coating surface, and then the titanium alloy was taken out. The obtained sample was recorded as MAO-TA24-hydrothermal treatment sample; Wherein, the alkali solution is 4wt% sodium hydroxide aqueous solution.
[0027] (2) Preparation of MAO-TA24-CuS complex sample The titanium alloy was immersed in a dithiothreitol (DTT) diluent, and the pH of the dithiothreitol diluent was adjusted to 6.50 with sodium hydroxide. The mixture was stirred at room temperature for 30 minutes to introduce nanoscale microstructures and hydroxyl groups on the surface of the ceramic membrane. The titanium alloy was taken out and stored at 4°C for later use. The obtained sample was recorded as a MAO-TA24-CuS complex sample.
[0028] The molar concentration of the dithiothreitol diluent is 0.033 mol / L. The preparation process is as follows: 50 mL (0.1 mol / L) of dithiothreitol solution and 100 mL of ultrapure water are added into a beaker and mixed to prepare the dithiothreitol diluent.
[0029] Step 4: Hydrogel coating: (1) The preparation process of prepolymer solution is as follows: Chitosan and [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide (SBMA) were dissolved in water to form a mixed solution; α-ketoglutaric acid and acrylic acid (AAc) were then added to the mixed solution, and reacted at room temperature for 10 minutes under a nitrogen atmosphere to obtain a slightly yellow viscous liquid; finally, the bubbles in the slightly yellow viscous liquid were eliminated by ultrasonication for 5 minutes to obtain a prepolymer solution; In the mixed solution, the mass ratio of chitosan to water is 1:100 (i.e., 1 g of chitosan is added to 100 g of water), the molar concentration of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide is 3 mol / L; the molar ratio of α-ketoglutaric acid to acrylic acid is 1:100; and the molar ratio of acrylic acid to [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide is 5:100.
[0030] (2) Preparation of MAO-TA24-OH-p(AA-SBMA) / CS sample The prepolymer solution is coated on the titanium alloy after the hydrothermal treatment, and the reaction is carried out under ultraviolet light for 8 hours to obtain a first network gel, thereby obtaining a coating; (3) Preparation of MAO-TA24-OH-p(AA-SBMA) / CS-β-GP DN sample The first network gel was immersed in a β-glycerophosphate sodium salt solution for 4 hours to form an ionic-covalent double network p(SBMA-co-AAc) / CS-β-GP DN hydrogel, thus obtaining a post-treated coating.
[0031] Comparative Example 1: TA24 sample after polishing Sample obtained by only processing in step 1 of Example 1: polished TA24 specimen.
[0032] Comparative Example 2: MAO-TA24 (10 minutes) sample The sample prepared by the treatment of step 1-step 2 of Example 1: MAO-TA24 (10 minutes) sample.
[0033] Comparative Example 3: MAO-TA24-Hydrothermal Treatment Sample The sample prepared by the treatment of step 1 to step 3 (1) of Example 1: MAO-TA24-hydrothermally treated sample.
[0034] Comparative Example 4: MAO-TA24-CUS complex sample The sample prepared by the treatment of step 1 to step 3 (2) of Example 1: MAO-TA24-CUS complex sample.
[0035] Comparative Example 5: MAO-TA24-OH-p(AA-SBMA) / CS Sample The sample prepared by processing step 1 to step 4 (2) of Example 1 is: MAO-TA24-OH-p(AA-SBMA) / CS sample.
[0036] Comparative Example 6: MAO-TA24-Hydrothermal Treatment-SHS Sample The sample prepared by treating the step 1 to step 3 (1) of Example 1 was immersed in a silane solution for 4 hours and then baked at 100° C. for 60 minutes to obtain a super hydrophobic surface.
[0037] The silane solution was prepared by adding 0.1 ml of 1H,1H,2H,2H-perfluorooctyltrichlorosilane into 100 ml of ethanol solvent.
[0038] 2. Performance tests of the embodiments and comparative examples: (1) SEM morphology of titanium alloy surface under different treatment processes: Figure 1 The SEM morphology of titanium alloy surface under different treatment processes. Figure 1 (a)- Figure 1(c) SEM morphology images of polished TA24 sample, MAO-TA24 (10 minutes) sample, and MAO-TA24-hydrothermal treatment sample, respectively; Figure 1 (a) shows that the surface of TA24 sample is relatively smooth after polishing.
[0039] Figure 1 (b) shows that after polishing and micro-arc oxidation treatment, there are a large number of micropores and microcracks on the surface of the micro-arc oxidation coating of the MAO-TA24 (10 minutes) sample.
[0040] Figure 1 (c) shows that after polishing, micro-arc oxidation treatment and hydrothermal treatment, the MAO-TA24-hydrothermal treatment sample forms nanothorns on the porous surface and inside. At this time, the coating surface of the titanium alloy is porous and thorny.
[0041] (2) FTIR-ATR (Fourier transform infrared spectroscopy) images of titanium alloy surface coatings under different treatment processes: Figure 2 FTIR-ATR (Fourier transform infrared spectroscopy) diagram of titanium alloy surface coating under different treatment processes; Figure 2 The FTIR-ATR graphs are respectively of MAO-TA24 (10 minutes) sample and MAO-TA24-hydrothermally treated sample (Figure a), DTT drug and MAO-TA24-CUS complex sample (Figure b), MAO-TA24-OH-p(AA-SBMA) / CS sample and MAO-TA24-OH-p(AA-SBMA) / CS-β-GPDN sample (Figure c).
[0042] Figure 2 (a) shows that the FTIR-ATR graph of MAO-TA24 is a straight line, indicating that a ceramic layer is formed on the surface of the micro-arc oxidation, while the MAO-TA24-hydrothermal treatment has a linear trend at 3231 cm -1 An absorption peak appeared at , indicating that the porous thorn surface of the titanium alloy contains a large number of -OH groups.
[0043] Figure 2 (b) shows that the characteristic peaks of the MAO-TA24-CUS complex sample are the same as those of the ligand DTT. However, compared with the FT-IR of DTT, the MAO-TA24-CUS complex sample has a peak at 2554 cm -1 The SH stretching vibration peak disappears, indicating that the Cu 2+ It reacts with the sulfhydryl bond in dithiothreitol to form a Cu-S complex. Figure 2(c) shows: FT-IR spectrum of MAO-TA24-OH-p(AA-SBMA) / CS sample, 1750cm -1 The absorption peak intensity at 1182 cm -1 The absorption peak at 1729 cm -1 The sharp singlet at 1039 cm -1 The absorption peak at 1483 cm -1 At 962-526 cm -1 The peaks in the range of 3445cm are attributed to the vibration of CH and CC bonds in the polymer backbone. -1 The stretching vibration peak of hydroxyl (-OH) is at 929cm -1 The bending vibration peak of –OH at can confirm the existence of –COOH, indicating that the first network polymer p(AA-SBMA) is formed.
[0044] In the FT-IR graph of the MAO-TA24-OH-p(AA-SBMA) / CS-β-GP DN sample, new absorption peaks appeared. The broad peak at 3600-3000 cm⁻¹ was attributed to the stretching vibration of -OH. There are a large number of hydroxyl groups in chitosan, and saturated glycerophosphate also contains hydroxyl groups. Their -OH stretching vibrations are superimposed, and the peak is broadened due to interactions such as hydrogen bonds, so a broad peak appears at 3600-3000 cm⁻¹, and 2223-2074 cm⁻¹ is attributed to some unsaturated bonds (C≡C, C≡N, etc.) or the stretching vibration of accumulated double bonds, indicating that the amino group of chitosan can form an ionic cross-linked network with negatively charged phosphates through "binary" coordination bonds (MAO-TA24-OH-p(AA-SBMA) / CS-β-GP DN), thereby An absorption peak appears at 2074cm⁻¹. The density of the "binary" coordination bonds is large, so the network is more rigid and more stable in water. During the deformation of the gel, the ionic covalent network dissipates energy more easily, thereby enhancing the toughness of the hydrogel.
[0045] (3) Pollution of titanium alloy surfaces under different treatment processes after 45 days of offshore hanging test: Figure 3 This is a diagram showing the pollution status of titanium alloy surfaces treated with different processes after 45 days of offshore hanging test; Figure 3 (a)-(c) show the results of the polished TA24 sample, the MAO-TA24 (10 minutes) sample, and the MAO-TA24-OH-p(AA-SBMA) / CS-β-GP DN sample, respectively.
[0046] Figure 3 (a) shows that after polishing, a large amount of algae and large pollutants such as barnacles are attached to the surface of the TA24 sample, and the anti-fouling effect is poor.
[0047] Figure 3 (b) shows that the titanium alloy MAO-TA24 sample treated by micro-arc oxidation (10 minutes) has fewer barnacles attached to its surface, but more algae and tubeworms attached to its surface; Figure 3 (c) shows that after micro-arc oxidation treatment, hydrothermal treatment and super-hydrophobic treatment, the titanium alloy MAO-TA24-hydrothermal treatment-SHS sample has no obvious barnacles and tubeworms attached to its surface, and the surface fouling is mainly algae attached; Figure 3 (d) shows that there are no obvious fouling organisms on the surface of the titanium alloy MAO-TA24-OH-p(AA-SBMA) / CS-β-GP DN sample after micro-arc oxidation, hydrothermal treatment and hydrogel coating, and the composite coating coated with hydrogel has excellent anti-fouling properties.
[0048] (4) Friction behavior of titanium alloy surfaces under different treatment processes in artificial seawater: Figure 4 Stribeck curves of titanium alloy surfaces in artificial seawater under different treatment processes. Figure 4 The four lines in the figure show the results of sample No. 1 to sample No. 4, which correspond to the polished TA24 sample, MAO-TA24 (10 minutes) sample, MAO-TA24-hydrothermal treatment sample, and MAO-TA24-OH-p(AA-SBMA) / CS-β-GP DN sample.
[0049] The friction curve test process is as follows: four different samples (No. 1 is TA24, No. 2 is MAO-TA24 sample, No. 3 is MAO-TA24-hydrothermal treatment sample, No. 4 is MAO-TA24-OH-p(AA-SBMA) / CS-β-GP DN sample) are tested for friction performance by a reciprocating friction and wear tester. The sliding wear test is carried out on a specific friction and wear tester. The grinding material is a Si3N4 ball with a diameter of 5mm, which is reciprocated on the surface of the sample. During the test, the parameters of constant load 10N, swing stroke 4mm, frequency 2Hz, and sliding time 0.5h (total sliding distance 28.8m) are set.
[0050] Figure 4The black line shows that the surface of polished TA24 is relatively smooth, but in the early stage of friction, due to the adsorption of surface atoms, the formation and destruction of oxide films, the friction coefficient fluctuates significantly. As the friction process continues, the surface gradually reaches a dynamic equilibrium state, and the friction coefficient tends to be stable. After 1800s of the test, the friction coefficient of sample No. 1 reaches 0.369; Figure 4 The red line shows: TA24 (MAO-TA24 sample) after micro-arc oxidation has a porous surface morphology. At the beginning of friction, these pores will affect the contact state between the grinding ball and the sample surface, and the friction coefficient fluctuates. As the friction progresses, the pores are partially smoothed or filled, the contact state gradually stabilizes, and the friction coefficient also tends to stabilize. The porous structure enables it to have a certain ability to store lubricants or wear debris during the friction process. Compared with sample No. 1, the final stable friction coefficient is slightly lower. After the test was carried out for 1800s, the friction coefficient of No. 2 was 0.337.
[0051] Figure 4 The blue line shows that the surface of the sample treated with sodium hydroxide (MAO-TA24-hydrothermally treated sample) is porous and needle-like. This special microstructure makes the contact between the sample and the grinding ball more stable. After a small fluctuation in the initial stage, the friction coefficient remains basically unchanged. The needle-like structure may play a certain role in supporting and stabilizing the contact, reducing the relative sliding and friction coefficient changes during the friction process. Compared with sample No. 2, its friction coefficient is lower. After the test was carried out for 1800s, the friction coefficient of No. 3 was 0.305.
[0052] Figure 4 The green line shows: the titanium alloy MAO-TA24-OH-p(AA-SBMA) / CS-β-GP DN sample that has been micro-arc oxidized, hydrothermally treated and hydrogel-coated, the hydrogel coating plays a lubricating and buffering role during the friction process. In the initial stage, the friction coefficient fluctuated due to factors such as the running-in of the coating and the grinding ball. Over time, the coating gradually exerted a stable lubricating effect, which reduced the fluctuation of the friction coefficient and eventually stabilized at the lowest value, lower than the other three samples. This is because the hydrogel can effectively reduce the friction between the grinding ball and the sample surface, reducing energy loss and surface damage during friction. After the test was carried out for 1800s, the friction coefficient of No. 4 was 0.283.
[0053] In summary, compared with the prior art, the method for preparing a high-bonding anti-fouling and drag-reducing coating for a titanium alloy substrate provided in the present application includes the following design concepts and beneficial effects: 1. Conception: This application first uses micro-arc oxidation technology to treat titanium alloys, and in situ grows a dense and uniform ceramic film on the surface of the titanium alloy substrate (such as a titanium alloy pipe). The film layer is firmly bonded to the titanium alloy substrate and has no interface defects, thereby enhancing the stability and durability of the film layer. Subsequently, the surface structure after micro-arc oxidation is changed through hydrothermal treatment technology, and nano-scale microstructures and hydroxyls are introduced on the surface of the ceramic film. The multi-level structure greatly increases its specific surface area, laying the foundation for the subsequent adsorption and reaction of organic molecules. Dithiothreitol (DTT) also has -SH (thiol) groups. In the above reaction, these thiol groups react chemically with the copper ions on the surface of the titanium alloy after hydrothermal treatment to form Cu-S bonds and high-density covalent bonds, so that there will be a large number of hydroxyls on the surface, using covalent action and substrate anchoring effect (porous structure) to lay the foundation for the high-strength adhesion of the hydrogel to the titanium alloy substrate. The coating is applied to the surface of the treated titanium alloy pipe. In the first layer of the network, under the excitation of ultraviolet light, C = C in the acrylic acid molecule and C = C in sulfobetaine undergo free radical polymerization. These free radicals will trigger the opening of the C = C double bond in sulfobetaine, and then connect with the double bonds of other acrylic acid molecules to form a polymer chain. C - C covalent bonds are formed during the polymerization process, which builds part of the network. Sulfobetaine contains active groups (such as sulfonic acid groups, etc.) and forms hydrogen bonds with acrylic acid (carboxylic acid groups, etc.), thereby participating in the construction of the network. The hydroxyl groups of chitosan interact with the active groups of other molecules through hydrogen bonds, further stabilizing the network structure. In the second layer of the network, active groups such as phosphate in sodium glycerophosphate react with the active sites (amino groups of chitosan) in the first layer of the network, and the phosphate groups form salt bonds with the amino groups of chitosan, thereby building a second layer of the network on the basis of the first layer of the network, forming a double network hydrogel. The hydroxyl groups (-OH) in the hydrogel and the hydroxyl groups on the surface of the micro-arc oxidation layer can form hydrogen bonds. In the process of building a multilayer structure, it can play a strong connecting role and enhance the stability of the overall structure. For example, the -OH in the acrylic polymer chain forms a hydrogen bond with the -OH on the surface of the micro-arc oxidation layer, making the bond between the hydrogel layer and the micro-arc oxidation layer tighter. The double network hydrogel contains zwitterionic polymers, which can firmly bind water molecules through ion solvation to form a hydration layer physical barrier, effectively preventing the adhesion of other molecules and fouling organisms.
[0054] Due to the unique electrical neutrality of zwitterions in the prepared MAO-TA24-OH-p(AA-SBMA) / CS-β-GP DN hydrogel, the possibility of sea mud particles adsorbing to the hydrogel surface through ion coupling was avoided. In addition, the hydration layer formed by zwitterions played a lubricating role between the fluid and the solid surface, transforming the direct contact between the fluid and the solid surface into liquid-liquid contact, thereby significantly reducing the interfacial friction and achieving the drag reduction effect of the titanium alloy substrate used in the seawater environment.
[0055] Compared with existing hydrogel coatings, the innovative points are as follows: micro-arc oxidation, hydrothermal treatment, dithiothreitol modification and double-layer network hydrogel coating are combined. Micro-arc oxidation generates a ceramic layer in situ on the surface of the material, which is firmly bonded to the substrate. Hydrothermal treatment further optimizes the surface structure. Dithiothreitol modification enhances the chemical bonding between the hydrogel and the underlying layer. Compared with ordinary hydrogel coatings, its bond with the anti-fouling surface is more stable and not easy to fall off. The surface after micro-arc oxidation and hydrothermal treatment has improved hardness and wear resistance, and the double-layer network hydrogel structure has good stability itself, which can better resist erosion and damage from external environmental factors and extend the service life of the coating. The double-network hydrogel has good hydrophilicity and can effectively prevent the attachment of fouling, while the multi-layer structure and modification treatment further enhance its anti-fouling performance.
[0056] 2. This application has the following beneficial effects: (1) The present application scheme enhances the mechanical properties of the coating and improves the stability and durability of the coating (MAO-TA24-OH-p(AA-SBMA) / CS-β-GP DN hydrogel) applied to the titanium alloy substrate, that is, the coating has long-term stable antifouling performance; (2) Achieved high-strength bonding between the antifouling coating and the titanium alloy substrate; (3) The coating (MAO-TA24-OH-p(AA-SBMA) / CS-β-GP DN hydrogel) applied to the titanium alloy substrate forms a hydration layer physical barrier, which can effectively prevent the adhesion of other molecules and fouling organisms. The coating applied to the titanium alloy substrate has excellent antifouling effect; (4) The unique electrical neutrality of the zwitterions of the prepared MAO-TA24-OH-p(AA-SBMA) / CS-β-GP DN hydrogel avoids the possibility of sea mud particles being adsorbed onto the hydrogel surface through ionic coupling, making the coating have excellent antifouling effect.
[0057] (5) The hydration layer formed by the zwitterions of the prepared MAO-TA24-OH-p(AA-SBMA) / CS-β-GP DN hydrogel plays a lubricating and drag-reducing role between the fluid and the solid surface, making the coating have an excellent drag-reducing effect.
[0058] It should be noted that: Stribeck meaning: In the Stribeck curve, Stribeck uses the friction coefficient m as the ordinate and the abscissa (lubricant viscosity × sliding speed) / load to illustrate several lubrication methods. (This can be removed. When changing equipment, this formula is not used.) In this article, “~” is used to indicate a numerical range, and the range indicated by this expression includes two endpoint values.
[0059] The specific parameters or some commonly used reagents or raw materials in the above embodiments are specific embodiments or preferred embodiments of the present application, but are not intended to limit the present application. Those skilled in the art may make adaptive adjustments within the scope of the present application.
[0060] In addition, unless otherwise specified, the raw materials used may also be conventional commercial products in the art, or prepared by conventional methods in the art; that is, the reagents and instruments used in this embodiment are not indicated with information such as the manufacturer, and are all conventional products that can be purchased on the market.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a high-bonding anti-fouling and drag-reducing coating for a titanium alloy substrate, characterized in that: The following steps are involved: Micro-arc oxidation: Micro-arc oxidation treatment is performed on titanium alloy to form a ceramic film on the surface of the titanium alloy; Hydrothermal treatment: subjecting the titanium alloy after micro-arc oxidation treatment to a hydrothermal reaction, introducing nano-scale porous thorn microstructures and hydroxyl groups on the surface of the ceramic membrane; Hydrogel coating: coating the prepolymer solution on the titanium alloy after hydrothermal treatment, and irradiating the reaction under ultraviolet light to obtain the first network gel; The prepolymer liquid is a yellowish viscous liquid formed by the reaction of the mixture at room temperature under a protective atmosphere; the mixture is a mixed solution formed by mixing chitosan, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide, α-ketoglutaric acid, and acrylic acid in water.
2. The method for preparing a high-bonding anti-fouling and drag-reducing coating for a titanium alloy substrate according to claim 1, characterized in that: After forming the first network gel, post-processing the first network gel; The post-treatment process is: immersing the first network gel in a β-glycerophosphate sodium salt solution to form an ionic-covalent double network p(SBMA-co-AAc) / CS-β-GP DN hydrogel.
3. The method for preparing a high-bonding anti-fouling and drag-reducing coating for a titanium alloy substrate according to claim 2, characterized in that: The prepolymer solution is coated on the titanium alloy after hydrothermal treatment, and the reaction is carried out under ultraviolet light for 7 to 12 hours to obtain a first network gel; the first network gel is immersed in a β-glycerophosphate sodium salt solution for 0.5 to 8 hours to form an ionic-covalent double network p(SBMA-co-AAc) / CS-β-GP DN hydrogel; Wherein, the preparation process of the prepolymer solution is: Dissolve chitosan and [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide in water to form a mixed solution; then add α-ketoglutaric acid and acrylic acid to the mixed solution, react at room temperature for 10 to 20 minutes under a nitrogen atmosphere to obtain a slightly yellow viscous liquid, and finally eliminate bubbles in the slightly yellow viscous liquid to obtain a prepolymer solution; In the mixed solution, the mass ratio of chitosan to water is 1 to 10:100, and the molar concentration of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide is 1 mol / L to 5 mol / L; The molar ratio of the α-ketoglutaric acid to the [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide is 0.1 to 2:100; the molar ratio of the acrylic acid to the [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide is 1 to 10:
100.
4. The method for preparing a high-bonding anti-fouling and drag-reducing coating for a titanium alloy substrate according to claim 1, characterized in that: The micro-arc oxidation treatment process is as follows: placing an electrolyte in an electrolytic cell, then placing a titanium alloy in the electrolyte as an anode, and a metal sheet in the electrolytic cell as a cathode; The bipolar pulse micro-arc oxidation power supply is started to perform micro-arc oxidation treatment; and then the titanium alloy is cleaned; The electrolyte temperature during the micro-arc oxidation process was lower than 20°C, and a constant current mode was used throughout the process with a current density of 0.5-2 mA / cm 2 , frequency is 300~2000Hz, duty cycle is 3~10%, deposition time is 300~1200s, and termination voltage is 400~650V.
5. The method for preparing a high-bonding anti-fouling and drag-reducing coating for a titanium alloy substrate according to claim 4, characterized in that : The components of the electrolyte include silicate, glycerol, potassium fluoride, phosphate, sodium hydroxide and water; Wherein, in the electrolyte, the concentrations of silicate, glycerol, potassium fluoride, phosphate and sodium hydroxide are 5-15 g / L, 3-9 g / L, 0-10 g / L, 0-5 g / L and 5-15 g / L respectively; Wherein, the material of the metal sheet is stainless steel.
6. The method for preparing a high-bonding anti-fouling and drag-reducing coating for a titanium alloy substrate according to claim 1, characterized in that: The process of the hydrothermal reaction is: The titanium alloy after micro-arc oxidation treatment is immersed in an alkaline solution preheated to 20-60°C, and immersed at 20-60°C for 0.5-4h; then the titanium alloy is taken out and immersed in a dithiothreitol dilution, and the pH of the dithiothreitol dilution is adjusted to 6-6.5 with alkali, and stirred at room temperature for 10-60min, so that nano-scale microstructures and hydroxyl groups are introduced into the surface of the ceramic membrane.
7. The method for preparing a high-bonding anti-fouling and drag-reducing coating for a titanium alloy substrate according to claim 6, characterized in that: During the hydrothermal reaction, the pH of the dithiothreitol dilution solution is adjusted with sodium hydroxide; The alkali solution is a 1-8 wt% sodium hydroxide aqueous solution; the molar concentration of the dithiothreitol diluent is 0.01-0.05 mol / L; After the hydrothermal reaction is completed, the titanium alloy is taken out and stored at low temperature for later use.
8. The method for preparing a high-bonding anti-fouling and drag-reducing coating for a titanium alloy substrate according to claim 1, characterized in that: Before micro-arc oxidation treatment, the titanium alloy surface is polished and cleaned in sequence.
9. A high-bonding anti-fouling and drag-reducing coating for a titanium alloy substrate, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. Application of the high-bonding anti-fouling and drag-reducing coating for titanium alloy substrates as claimed in claim 9 in the surfaces of ships, bridges, docks, offshore platforms, petroleum, chemical industry, transportation, aviation and various titanium metal structures.
Citation Information
Patent Citations
Titanium alloy surface anti-fouling composite coating as well as preparation method and application thereof
CN113005497A
Titanium alloy wear-resistant and antibacterial composite coating suitable for marine environment and preparation method of titanium alloy wear-resistant and antibacterial composite coating
CN114318467A
Mixed metal oxide coatings for titanium alloys
EP4353866A1
Composite membrane, preparation method thereof, anode structure including the composite membrane, and lithium secondary battery including the anode structure
US20160181585A1
Cited By
3D printing metal implant with synergistic effect and preparation method thereof
CN121197510A
Surface treatment method for titanium alloy 3D printing piece
CN121360825A
Surface treatment method for titanium alloy 3D printed part
CN121360825B